The sociological conception of corruption: a case study of Karnataka Lokayukta. Issue 5 (19th October 2020) - Shetty, Madhukar K.; Verma, Arvind; Cherukuri, Suvarna
ABSTRACT: Modern states have to reckon with the problem of corruption because of its derailing influence on the functioning of government. This paper argues that state–society relations frame the context in which the incidence of corruption and the state's response to corruption become mutually reinforcing processes. We define this as "structures of irresolution" wherein an idealized abstract image of the state is constructed and corruption is blamed upon individual aberrations rather than the deviant nature of the state itself. We apply this framework to examine the functions of Karnataka Lokayukta, an anticorruption institution in India. Our data comes from the Annual Reports of this Lokayukta between 1987 and 2015 and corruption cases from Crime in India statistics. Our analysis shows that Lokayukta targeted officials disproportionately from lower sections of the bureaucracy. We recommend decentralized accountability mechanisms that redefine the relations between the individual, institutions, and the state to combat corruption effectively.